Development and experimental verification of control system model with professional competence formation for future teachers of informatics in the professional preparation process - Girka, I. (Problems of Engineer-Pedagogical Education, 2018)
The article is devoted to the analysis of management professional competence formation of future teachers of informatics that includes aims and objects, scientific attitude, principles, functions, principal stage, subject and object, criteria, descriptor, level and control objectiveand provides development of management object, achievements of effective result and creation of such terms for future specialists that would promote their professional and personality development. Also the article is considered and experimentally-verified the objective model of control system with professional competence formation of future teachers of informatics in the professional preparation process which consist of structural components:methodological-goals, rich in content, process,evaluation-diagnostic and analytically-effective. The organizationally-pedagogical terms of management professional competence formation of future teachers of informatics during the professional preparation: activation of cognitive, practical and teaching activity is reasonable.